Threshold concepts encountered by second year medical students in a Basic Health Science module; a qualitative study - Mansoor, Memoona; Tayyab, Ali; Shah, Syed Shoaib; Sarfraz, Rehmah (Journal of the Pakistan Medical Association, 2022)
Objective: To explore threshold concepts in a Basic Health Sciences module. Method: The qualitative study was conducted at the Islamabad Medical and Dental College, Islamabad, Pakistan, in March 2019, and comprised students and faculty members in the gastrointestinal tract module of spiral I of the integrated modular curriculum in Basic Health Sciences. Data on student experiences was collected using semi-structured interviews with open-ended questions. The data was coded and themes were identified by the researchers independently. A thematic matrix was produced, cross-referencing data relating to troublesome areas identified by the students against the threshold concept criteria. The identified themes were discussed among the researchers to reach consensus. Only the identified themes were taken as the expected threshold concepts in the gastrointestinal tract module. Results: Of the 18 subjects, 14(77.8%) were students and 4(22.2%) were facilitators. There were 8 areas identified by the students as troublesome in the module; development of gastrointestinal tract, anatomical relations, electron transport chain, histology of gastrointestinal tract mucosa, peritoneal disposition, anal canal and ischioanal fossae, peristalsis, and absorption across gastrointestinal tract mucosa. Only development of gastrointestinal tract appeared to cross-match with all the criteria outlined for threshold concepts. The troublesome areas identified by the teachers were development of gastrointestinal tract, peritoneal disposition, anatomical relations, absorption across gastrointestinal tract and peristalsis. Conclusion: Development of gastrointestinal tractwas found to be the threshold concept in the system-based integrated module of gastrointestinal tract. Most of the students found their previous knowledge inadequate in learning concepts of the module.